Supernumerary Teeth - A Statistical Survey - J Rema; Anita Balan; Nileena R Kumar (Wolters Kluwer Medknow Publications, 2007)
Supernumerary teeth are those that are additional to the normal complement. They may develop in any region of dental arch, but are most common in the anterior maxilla. Even though many have described supernumerary teeth, little work has been conducted to determine the incidence of supernumerary teeth in the population of Kerala, India. The following study was conducted in an attempt to find out the incidence of supernumerary teeth in patients reporting to the Dental College Trivandrum. Out of 28192 patients screened 83 patients had supernumerary teeth giving an incidence of 3%. The observations of the preliminary study may form a base line data for further work in this field.